2006
DOI: 10.1104/pp.106.081943
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Induced Anther Indehiscence in Cotton Is Partially Temperature Dependent and Involves Cytoskeleton and Secondary Wall Modifications and Auxin Accumulation

Abstract: Yield reduction caused by late application of glyphosate to glyphosate-resistant cotton (Gossypium hirsutum; GRC) expressing CP4 5-enol-pyruvylshikmate-3-P synthase under the cauliflower mosaic virus-35S promoter has been attributed to male sterility. This study was aimed to elucidate the factors and mechanisms involved in this phenomenon. Western and tissue-print blots demonstrated a reduced expression of the transgene in anthers of GRC compared to ovules of the same plants. Glyphosate application to GRC grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…This treatment induced the accumulation of high levels of indole-3-acetic acid, and flowers exhibited delayed anther dehiscence due to changes in cell wall lignification of endothecium cells (Yassuor et al, 2006). This study was designed to confirm and extend our previous suggestion that auxin plays a key role in regulating the late stages of stamen development (Cecchetti et al, 2004).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This treatment induced the accumulation of high levels of indole-3-acetic acid, and flowers exhibited delayed anther dehiscence due to changes in cell wall lignification of endothecium cells (Yassuor et al, 2006). This study was designed to confirm and extend our previous suggestion that auxin plays a key role in regulating the late stages of stamen development (Cecchetti et al, 2004).…”
Section: Introductionsupporting
confidence: 59%
“…Additional indirect evidence comes from a study by Yassuor et al (2006) on cotton (Gossypium hirsutum) and Arabidopsis thaliana flowers treated with the herbicide glyphosate. This treatment induced the accumulation of high levels of indole-3-acetic acid, and flowers exhibited delayed anther dehiscence due to changes in cell wall lignification of endothecium cells (Yassuor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in morning glory have revealed population variability in the survival of glyphosate application and surviving plants often have functionally female flowers due to abnormal stamens [29]. Similarly, studies in cotton have shown glyphosate-induced changes in microtubules in anthers, leading to poor dehiscence [30], possibly similar to the mechanism contributing to the reduction in anther dehiscence we observed. Glyphosate resistant corn and cotton varieties that have reduced transgene expression in male tissues also suffer from shortened anther filaments leading to reduced pollen transfer between anther and pistil [31] and reduced pollen viability [32].…”
Section: Discussionmentioning
confidence: 60%
“…dehiscence program (Yasuor et al, 2006). Our observation reveals that microtubules in csi1 cells are depolymerized more rapidly under dehydration for 4 to 12 h (this time period is sufficient for anther dehydration, bud opening, and anthesis in wild-type anthers) (Smyth et al, 1990).…”
Section: Discussionmentioning
confidence: 71%